Madness, Melancholy, and Mental Health: A Comparative Study of Shakespeare and Thomas Hardy (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper explores the representation of mental health in the works of William Shakespeare and Thomas Hardy, examining how literature reflects psychological distress across different historical and social contexts. While Shakespeare’s tragedies, particularly Hamlet, Macbeth, and King Lear, depict madness, grief, and emotional conflict through dramatic intensity and philosophical inquiry, Hardy’s novels, such as Tess of the d’Urbervilles and Jude the Obscure, present a more grounded and deterministic portrayal of mental suffering shaped by social constraints and existential despair. The study adopts an interdisciplinary approach, integrating literary analysis with psychological perspectives to understand how themes of anxiety, depression, trauma, and isolation are articulated in these texts. Shakespeare often presents mental instability as a complex interplay of internal conflict, moral dilemmas, and external pressures, whereas Hardy emphasizes the impact of social injustice, rigid moral codes, and environmental forces on individual wellbeing. By comparing these two authors, the paper highlights the evolution of mental health representation from the Elizabethan era to the Victorian period, demonstrating a shift from symbolic and dramatic expressions of madness to more realistic and socially rooted depictions of psychological distress. The analysis also considers how language, narrative structure, and characterization contribute to the portrayal of mental states. Ultimately, this paper argues that literature serves as a powerful medium for understanding mental health, offering insights into human emotions and societal influences that remain relevant in contemporary discussions on wellbeing in higher education. Such literary explorations can contribute to fostering empathy, critical awareness, and holistic approaches to mental health in academic spaces.